1998
DOI: 10.1038/sj.bmt.1701497
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation as treatment for X-linked immunodeficiency with hyper-IgM

Abstract: Summary:We report a 10-year-old boy with a severe form of immunodeficiency with hyper-IgM who underwent successful bone marrow transplantation with his HLAmatched sister as donor. Busulfan (20 mg/kg) and cyclophosphamide (200 mg/kg) were used as conditioning. The post-transplant course was uneventful. He is alive 25 months later with full hematological and immunological reconstitution. Keywords: X-linked immunodeficiency with hyper-IgM; bone marrow transplantation; CD40 ligand X-linked immunodeficiency with hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Conservative management consists of immunoglobulin replacement therapy, prophylaxis against PJP, granulocyte‐colony stimulating factor (GCSF) for severely neutropenic patients, rCD40L therapy, and measures to decrease the risk of cryptosporidium infections, such as avoiding swimming in ponds and lakes and drinking boiled water . However, the only curative therapy is allogeneic hematopoietic stem cell transplantation (HSCT), as suggested by limited published data . Also, advances in diagnosis, donor selection, preparative regimens, and supportive care have led to improved outcomes following transplantation for primary immunodeficiencies .…”
Section: Introductionmentioning
confidence: 99%
“…Conservative management consists of immunoglobulin replacement therapy, prophylaxis against PJP, granulocyte‐colony stimulating factor (GCSF) for severely neutropenic patients, rCD40L therapy, and measures to decrease the risk of cryptosporidium infections, such as avoiding swimming in ponds and lakes and drinking boiled water . However, the only curative therapy is allogeneic hematopoietic stem cell transplantation (HSCT), as suggested by limited published data . Also, advances in diagnosis, donor selection, preparative regimens, and supportive care have led to improved outcomes following transplantation for primary immunodeficiencies .…”
Section: Introductionmentioning
confidence: 99%
“…8 Hematopoietic stem cell transplantation (HSCT) has the potential to cure this T-cell immunodeficiency. [9][10][11][12][13][14][15][16][17] A particular problem during transplantation is reactivation of cryptosporidial infection resulting in diarrhea and acute cholangiopathy. In a study using molecular techniques to detect asymptomatic carriage of cryptosporidial species in primary immunodeficiency patients, 5 of 12 patients with CD40 ligand deficiency were chronically colonized, of whom only 1 had a known history of infection.…”
Section: Cd40 Ligand (Cd40l) Deficiency (X-linked Hyper-immunoglobulimentioning
confidence: 99%
“…We could find only two reports describing B cell reconstitution after BMT of these patients. Duplantier et al [37] found that peripheral B cell numbers took some 20 months to return to normal following fully matched sibling BMT of an 8-month-old boy with XHIM, and Bordigoni et al [39] found that in a 10-year-old boy, B cell levels were normal 10 months after BMT. Looking at a large number of older, non-XHIM patients, Storek et al [41] reported that on average, B cell numbers were normal by 1 year after transplantation.…”
Section: Discussionmentioning
confidence: 99%